Beckett, Adorno, and the hope for nothingness as something: Meditations on theology in the age of its impossibility - Nosthoff, Anna-Verena (Critical research on religion, 2018)
This article discusses the theological implications of Adorno's writings on Beckett by specifically examining their constellative motifs of death, reconciliation, and redemption. It addresses not only their content but also their form, suggesting a mutually stimulating relationship between the two as based both on a negative-dialectical approach and an inverse-theological trajectory. Focusing on Adorno's discussion of Beckett's oeuvre as a "metaphysical entity," the author argues that Adorno's reading of Beckett is peculiar because it is inextricably tied to his own critical-theological venture. The article claims that Adorno's reflections on Beckett contain, at their most basic level, meditations on theology in the age of its impossibility.